Corporate Psychopaths, Bullying and Unfair Supervision in the Workplace - Boddy, Clive R. (2011)
This article reports on empirical research that establishes strong, positive, and significant correlations between the ethical issues of bullying and unfair supervision in the workplace and the presence of Corporate Psychopaths. The main measure for bullying is identified as being the witnessing of the unfavorable treatment of others at work. Unfair supervision was measured by perceptions that an employee’s supervisor was unfair and showed little interest in the feelings of subordinates. This article discusses the theoretical links between psychopathy and bullying and notes that little empirical evidence confirms the connection in management research. The sample of 346 Australian senior white collar workers used in the research is described as is the measure of behavior for identifying psychopaths. The findings are then presented and discussed showing that when Corporate Psychopaths are present in a work environment, the level of bullying is significantly greater than when they are not present. Further, that when Corporate Psychopaths are present, supervisors are strongly perceived as being unfair to employees and disinterested in their feelings. This article concludes that around 26% of bullying is accounted for by 1% of the employee population, those who are Corporate Psychopaths.
Keywords: Abusive supervision; Toxic leadership; Ethics; Bullying; Corporate Psychopaths